1999
DOI: 10.1029/1999gl005395
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a crack‐like conduit beneath the active crater at Aso Volcano Japan

Abstract: Abstract.To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 7 publications
8
67
1
1
Order By: Relevance
“…Recent magnetotelluric surveys have detected a significantly low resistivity region at approximately 200 m below the crater lake. An analysis of the longperiod tremor indicated that volcanic fluid is transported to the region through a crack-like conduit (Yamamoto et al, 1999). These results suggest that a hydrothermal system exists at a shallow depth (Kanda et al, in press).…”
Section: Implication For the Volcanic Hydrothermal Systemmentioning
confidence: 85%
See 1 more Smart Citation
“…Recent magnetotelluric surveys have detected a significantly low resistivity region at approximately 200 m below the crater lake. An analysis of the longperiod tremor indicated that volcanic fluid is transported to the region through a crack-like conduit (Yamamoto et al, 1999). These results suggest that a hydrothermal system exists at a shallow depth (Kanda et al, in press).…”
Section: Implication For the Volcanic Hydrothermal Systemmentioning
confidence: 85%
“…Various geophysical observational studies, including seismicity (Yamamoto et al, 1999) and geomagnetic field (Tanaka, 1993), have been carried out with the aim of determining the ascent processes of the volcanic fluid or magma at Aso volcano. These have revealed that the sources are located at shallow depths below Yudamari.…”
Section: Introductionmentioning
confidence: 99%
“…Tsutsui et al (2003) observed a high-velocity zone considered to be a dike or dense volcanic deposits beneath Kusasenrigahama to the Nakadake crater; therefore, magma from a magma storage region could not ascended directly above this area. Yamamoto et al (1999) showed a dike model conduit beneath the Nakadake craters with a reasonable dip range of 83°-86°W. This dike probably has been created by connection faulting between Aso-N·C and Aso-S by westward dragging.…”
Section: Magma Plumbing System With Faultsmentioning
confidence: 99%
“…The results from studies of volcanic tremors occurring at active volcanoes indicate that volcanic fluid or magma is related to the source mechanisms of the volcanic activity (e.g., Tameguri et al, 2007;Mori et al, 2008). Based on such results, it has been suggested that the source mechanisms of harmonic and long period tremors that have a resonant frequency are resonance phenomena occurring in the conduits or cracks filled with volcanic fluid or gas (e.g., Schlindwein et al, 1995;Yamamoto et al, 1999;Maryanto et al, 2008). However, the exact depth from the surface to the layer separating the vapor and liquid phases and to the magma head in a conduit cannot be obtained by geophysical prospecting or associated seismic observations.…”
Section: Introductionmentioning
confidence: 99%